MECHANISTIC EVALUATION OF RIGID AIRFIELD PAVEMENTS - GUCBILMEZ, E; YUCE, R (Asce-Amer Soc Civil Eng, 1995)
A structural deterioration relationship is developed using the U.S. Army Corps of Engineers accelerated traffic tests for plain concrete airfield pavements. The relationship predicts the performance of the rigid pavement in terms of the structural condition index from the pavement's Westergaard edge stresses, flexural strength, and number of load applications. The model is compared to other design criteria and unfailed test sections and gives reasonable agreement. The relationship between the structural condition index and the coverages at initial failure of the pavement is determined, and an alternative fatigue curve is suggested for use in the thickness design of rigid airfield pavements with joints capable of load transfer. The relationships developed only account for the tensile fatigue-loading-induced deterioration of the rigid airfield pavement. Actual in-service pavements will show additional deterioration because of other jointed rigid pavement distresses such as pumping, settlement or faulting, durability D cracking, pop-outs, scaling, or joint seal damage.